2016
DOI: 10.1002/pssb.201552760
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation of single‐crystal Bi2Te3 topological insulators grown with the Bridgman–Stockbarger method

Abstract: In this work, bismuth telluride (Bi 2 Te 3 ) single crystals were grown from melted polycrystalline Bi-Te material using the Bridgman-Stockbarger method. Crystalline quality and surface chemistry were investigated through X-ray diffraction analysis and X-ray photoelectron spectroscopy. The mechanical properties were investigated by means of depth-sensing nanoindentation tests carried out using the continuous stiffness measurement (CSM) technique. In turn, the distribution of material hardness and Young's modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
6
2
Order By: Relevance
“…This means that both the values of H and Ef of the Bi2Te3 thin films m otonically decrease with increasing TS. Noticeably, the H and Ef of the present Bi2Te3 films are significantly larger than that reported for the bulk Bi2Te3 (H = 1.6 ± 0.2 GPa E = 32.4 ± 2.9 GPa) [22]. The reason for the apparent discrepancy is not clear at pre Nevertheless, by comparing the results of the films in this study with that reported in [23], the stoichiometric levels and crystallite orientation of the films may have inti correlations with the H and Ef results.…”
Section: Resultscontrasting
confidence: 73%
“…This means that both the values of H and Ef of the Bi2Te3 thin films m otonically decrease with increasing TS. Noticeably, the H and Ef of the present Bi2Te3 films are significantly larger than that reported for the bulk Bi2Te3 (H = 1.6 ± 0.2 GPa E = 32.4 ± 2.9 GPa) [22]. The reason for the apparent discrepancy is not clear at pre Nevertheless, by comparing the results of the films in this study with that reported in [23], the stoichiometric levels and crystallite orientation of the films may have inti correlations with the H and Ef results.…”
Section: Resultscontrasting
confidence: 73%
“…3D topological insulators are considered a novel topological phase of matter, and are gaining growing interest from the worldwide scientific community [16][17][18], due to their promising applications in optoelectronics [19], plasmonics [20], spintronics [21], quantum computing [22], and thermoelectric devices [17,23,24]. Bi 2 Te 3 and Bi 2 Se 3 represent the most studied topological insulators, due to their large energy gap (~ 0.2-0.3 eV) that allows applications at room temperature [15,[25][26][27][28][29]. In this section we focus on Bi 2 Te 3 , a layered and anisotropic material, whose atomic structure is illustrated in Fig.…”
Section: Indentation Modulus Of Generally Anisotropic Topological Insmentioning
confidence: 99%
“…For both the directions parallel and perpendicular to the Bi 2 Te 3 lamellae, the experimental indentation modulus M E stabilizes when the penetration depth reaches a value of 120 nm. The stabilization is obtained only when the condition of full plasticity contact is satisfied, as discussed in [28].…”
Section: Indentation Modulus Of Generally Anisotropic Topological Insmentioning
confidence: 99%
“…Bismuth tellurides, especially Bi 2 Тe 3 , phases, and composites based on it have long been in the field of view of researchers as valuable thermoelectric materials [1][2][3]. After the discovery of a special quantum state of mattera topological insulator (TI) [4], it was found that Bi2Te3 and many other layered compounds of tetradimite-like structures are TI which are rather promising for their varied applications [5][6][7][8][9][10][11]. In particular, the unique optical properties make them promising for the use in broadband optoelectronics as photodetectors [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%